SGP film laminated glass and production process thereof
Modified polyurethane is prepared by the reaction of modified prepolymer and ethylenediamine, and combined with modified filler and SGP laminate resin to produce SGP film laminated glass, solving the problem of general thermal insulation effect of existing SGP film laminated glass and achieving better thermal insulation and ultraviolet absorption effects.
Patent Information
- Application Number
- CN202411695392.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-25
AI Technical Summary
At this stage, the thermal insulation effect of SGP film laminated glass is average and it is difficult to meet the high thermal insulation needs.
Pretreated polyurethane is prepared by reaction of modified prepolymer and ethylenediamine, and reacted with diphenylmethane diisocyanate, and modified polyurethane is prepared by adding N-(2-hydroxyethyl)maleimide. Then, hydrolyzed and condensed with the modified filler, dimethyldiethoxysilane and tetrabutyl titanate to obtain a modified resin, extruded and casted into a film with SGP laminated resin, and pressed at high temperature to prepare an SGP film laminated glass.
The combination of modified resin and SGP glue resin improves the thermal insulation effect of the glue film, and the multi-hole structure in the modified filler further enhances the thermal insulation performance. At the same time, the silicone segment and benzotriazole structure in the modified resin increase the absorption of ultraviolet rays and reduces ultraviolet ray irradiation.
Smart Images

Figure BDA0005151963680000141
Abstract
Description
Technical Field
[0001] The invention relates to the field of laminated glass preparation, and in particular to SGP film laminated glass and a production process thereof. Background Art
[0002] Laminated glass is a composite glass product made of two or more pieces of glass with one or more layers of organic polymer interlayer in between. After special high-temperature pre-pressing (or vacuuming) and high-temperature and high-pressure process treatment, the glass and the interlayer are permanently bonded together. Even if the glass is broken, the fragments will be stuck to the film, and the surface of the broken glass will remain clean and smooth. This effectively prevents the occurrence of stab injuries and penetration and falling incidents, ensuring personal safety. Most architectural glass uses laminated glass, not only to avoid injury accidents, but also because laminated glass has excellent anti-seismic intrusion capabilities. The interlayer can withstand continuous attacks from weapons such as hammers and chopping knives, and can also resist bullet penetration for a considerable period of time. Its safety precautions are extremely high. Among them, the commonly used interlayer films for laminated glass are: PVB, SGP, EVA, PU, etc., but the heat insulation effect generally affects the use of laminated glass. Summary of the invention
[0003] The object of the present invention is to provide a SGP film laminated glass and a production process thereof, which solves the problem that the heat insulation effect of the film in the current SGP film laminated glass is general.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A production process of SGP film laminated glass, specifically comprising the following steps:
[0006] Step S1: the modified prepolymer, ethylenediamine and DMF are mixed, nitrogen is introduced for protection, the reaction is carried out for 2-3 hours at a speed of 150-200 r / min and a temperature of 30-40° C., KH560 is added, the pH value is adjusted to 11-12, and the reaction is carried out for 3-5 hours to obtain a pretreated polyurethane; the pretreated polyurethane, diphenylmethane diisocyanate and DMF are mixed, nitrogen is introduced for protection, the reaction is carried out for 5-6 hours at a speed of 150-200 r / min and a temperature of 30-40° C., N-(2-hydroxyethyl)maleimide is added, and the reaction is continued for 4-6 hours to obtain a modified polyurethane;
[0007] Step S2: uniformly mix the modified polyurethane, modified filler, dimethyldiethoxysilane, ethanol and DMF, stir and add deionized water and hydrochloric acid at a speed of 120-150 r / min and a temperature of 65-70° C., react for 2-3 hours, add tetrabutyl titanate, continue to react for 2-3 hours, heat to 120-130° C., react for 3-5 hours, and obtain a modified resin; mix the modified resin, SGP laminated resin and diisopropylbenzene peroxide, extrude and cast into a film at a feeding section temperature of 190° C., a melting section temperature of 180° C., and a discharging section temperature of 150° C. to obtain a laminated sheet; place the laminated sheet between two pieces of glass, and press at high temperature to obtain SGP laminated glass.
[0008] The molar ratio of the isocyanate group and ethylenediamine on the modified prepolymer in step S1 is 1:1, and the molar ratio of the hydroxyl group, diphenylmethane diisocyanate and N-(2-hydroxyethyl)maleimide on the pretreated polyurethane is n:n:2, where n is a natural number greater than 1.
[0009] The amount ratio of the modified polyurethane, modified filler, dimethyldiethoxysilane, ethanol, DMF, deionized water, hydrochloric acid solution and tetrabutyl titanate described in step S2 is 5g:80mg:1mmo l:10mL:50mL:20mL:3mL:1.5mmo l, the mass fraction of the hydrochloric acid solution is 10%, and the weight ratio of the modified resin and the SGP interlayer resin is 30-50:80-100:1-3.
[0010] Further, the modified prepolymer is prepared by the following steps:
[0011] Step A1: p-chloro-o-nitroaniline, p-hydroxystyrene, sodium nitrite and potassium hydrogen sulfate are mixed uniformly and placed in a mortar, and ground for 20-30 minutes at a temperature of 20-25° C. to obtain an azo dye; the azo dye, ethanol and sodium hydroxide solution are mixed uniformly, and sodium dithionite is added under stirring at a speed of 600-800 r / min and a temperature of 80-85° C., and the mixture is reacted for 1-1.5 hours to obtain an intermediate 1;
[0012] Step A2: Mix magnesium metal, iodine and tetrahydrofuran evenly, introduce nitrogen protection, stir and add 2-bromothiophene at a speed of 60-80 r / min and a temperature of 20-25° C., raise the temperature to 60-70° C., and react for 3-5 hours to obtain intermediate 2; mix intermediate 1, intermediate 2 and tetrahydrofuran evenly, and react for 5-6 hours at a speed of 150-200 r / min and a temperature of 60-70° C. to obtain a modifier;
[0013] Step A3: uniformly mix the modifier, diethanolamine and DMF, introduce nitrogen protection, stir and add sodium hydroxide to a pH value of 10-11 at a speed of 120-150 r / min and a temperature of 20-25° C., react for 3-5 hours, adjust the pH to neutral, and obtain a modified monomer; mix the modified monomer, diphenylmethane diisocyanate and DMF, and react for 2-4 hours at a speed of 120-150 r / min and a temperature of 40-50° C. to obtain a modified prepolymer.
[0014] Furthermore, the molar ratio of p-chloro-o-nitroaniline, p-hydroxystyrene, sodium nitrite and potassium hydrogen sulfate in step A1 is 1:1.1:1:1, and the dosage ratio of azo dye, ethanol, sodium hydroxide solution and sodium dithionite is 25 mmol:50 mL:50 mL:82 mmol.
[0015] Furthermore, the amount ratio of magnesium metal, iodine, tetrahydrofuran and 2-bromothiophene in step A2 is 1.1 mol:1 mol:100 mL:1 mol, and the molar ratio of intermediate 1 to intermediate 2 is 1:1.
[0016] Furthermore, the molar ratio of the modifier described in step A3 to diethanolamine is 1:1, and the molar ratio of the modified monomer to diphenylmethane diisocyanate is 1:2.1.
[0017] Further, the modified filler is prepared by the following steps:
[0018] Step B1: Triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate and deionized water are uniformly mixed, and under the conditions of a rotation speed of 150-200 r / min and a temperature of 80-85° C., tetraethyl orthosilicate, KH550 and ethanol are added with stirring, and the reaction is carried out for 4-6 hours, and the supernatant is removed by centrifugation, and the substrate is added to a hydrochloric acid solution, and under the conditions of a frequency of 20-30 kHz and a temperature of 20-25° C., ultrasonic treatment is performed for 5-10 minutes, and then the temperature is raised to 60-70° C. and kept warm for 5-7 hours to obtain amino-modified nano-silica;
[0019] Step B2: Evenly mix the amino-modified nano-silica, tin tetrachloride and ethanol, stir and add deionized water and ammonia water to a pH of 10-12 at a speed of 120-150 r / min and a temperature of 30-40°C, stir for 10-15 minutes, heat to 150-160°C, react for 20-25 hours to obtain modified nano-silica, disperse the modified nano-silica in ethanol, introduce nitrogen protection, stir and add 3-isocyanatepropyltriethoxysilane at a speed of 300-500 r / min and a temperature of 30-40°C, react for 2-3 hours to obtain a modified filler.
[0020] Furthermore, the amount ratio of triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate, deionized water, tetraethyl orthosilicate, KH550 and ethanol in step B1 is 65 mg:380 mg:550 mg:25 mL:10 mmol:5 mmol:5 mL, the amount ratio of the base material and the hydrochloric acid solution is 1 mg:1 mL, and the mass fraction of the hydrochloric acid solution is 5%.
[0021] Furthermore, the dosage ratio of the amino-modified nano-silica, tin tetrachloride, ethanol and deionized water in step B2 is 2g:2mmo l:10mL:10mL, and the molar ratio of the amino group on the surface of the modified nano-silica to 3-isocyanatepropyltriethoxysilane is 1:1.
[0022] The invention has the beneficial effects as follows: the SGP film laminated glass prepared by the invention comprises the following steps: a modified resin and an SGP laminated resin are mixed and extruded and cast into a film to obtain a laminated sheet; the laminated sheet is placed between two pieces of glass and pressed at high temperature; the modified resin uses a modified prepolymer and ethylenediamine as raw materials, so that an isocyanate group on the modified prepolymer reacts with an amino group on the ethylenediamine to form an amino end-capping; the modified resin reacts with KH560, so that an epoxy group on the KH560 reacts with an amino group to obtain a pretreated polyurethane; the pretreated polyurethane reacts with diphenylmethane diisocyanate, so that a hydroxyl group on the pretreated polyurethane reacts with an isocyanate group on the diphenylmethane diisocyanate; the pretreated polyurethane is end-capped with N-(2-hydroxyethyl)maleimide to obtain a modified polyurethane; and the modified polyurethane, a modified filler, dimethyldiethoxysilane and tetrabutyl titanate are hydrolyzed and condensed to obtain a modified resin.
[0023] The modified prepolymer uses p-chloro-o-nitroaniline and p-hydroxybenzene as raw materials, forms an azo dye under the action of sodium nitrite and potassium bisulfate, treats the azo dye with sodium dithionite to form a benzotriazole structure, and obtains an intermediate 1; treats 2-bromothiophene with metal magnesium and iodine to form thienylmagnesium bromide, and obtains an intermediate 2; reacts the intermediate 1 with the intermediate 2, so that the chlorine atom site on the intermediate 1 reacts with the magnesium bromide group on the intermediate 2, and obtains a modifier; reacts the modifier with ethylene glycol amine, so that the double bond on the modifier and the secondary amine on the ethylene glycol amine are Michael-added, and obtains a modified monomer; and reacts the modified monomer with diphenylmethane diisocyanate, and obtains a modified prepolymer.
[0024] The modified filler is prepared by polycondensation of tetraethyl orthosilicate and KH550 as raw materials, and triethanolamine, hexadecyltrimethylammonium bromide and sodium trifluoroacetate are used as surfactants and template agents, so that the prepared nano-silica contains micropores to obtain amino-modified nano-silica. Tin tetrachloride is used as a raw material to embed tin dioxide in the micropores of the amino-modified nano-silica to obtain modified nano-silica. The modified nano-silica is reacted with 3-isocyanate propyltriethoxysilane to make the amino group on the modified nano-silica react with the isocyanate group on the 3-isocyanate propyltriethoxysilane to obtain the modified filler.
[0025] When the modified resin and SGP interlayer resin are melted, the double bonds on the modified resin can be grafted with the molecular chains on the SGP interlayer resin. The main body of the modified resin molecular chain is a polyurethane structure containing silicone segments, which can improve the thermal insulation effect of the SGP interlayer resin. The modified filler contains a multi-void structure, which further improves the thermal insulation effect. The titanium-containing silicone resin segments in the modified resin, the tin dioxide on the surface of the modified filler, and the benzotriazole structure in the modified resin can increase the absorption of ultraviolet rays by the interlayer sheet and reduce ultraviolet radiation. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] A production process of SGP film laminated glass, specifically comprising the following steps:
[0029] Step S1: the modified prepolymer, ethylenediamine and DMF are mixed, nitrogen is introduced for protection, the reaction is carried out for 2 hours at a speed of 150 r / min and a temperature of 30° C., KH560 is added, the pH value is adjusted to 11, and the reaction is carried out for 3 hours to obtain a pretreated polyurethane; the pretreated polyurethane, diphenylmethane diisocyanate and DMF are mixed, nitrogen is introduced for protection, the reaction is carried out for 5 hours at a speed of 150 r / min and a temperature of 30° C., N-(2-hydroxyethyl)maleimide is added, and the reaction is continued for 4 hours to obtain a modified polyurethane;
[0030] Step S2: The modified polyurethane, the modified filler, the dimethyldiethoxysilane, the ethanol and the DMF are mixed uniformly, and the mixture is stirred and deionized water and hydrochloric acid are added at a speed of 120 r / min and a temperature of 65° C. After reacting for 2 hours, tetrabutyl titanate is added, and the reaction is continued for 2 hours. The mixture is heated to 120° C. and reacted for 3 hours to obtain a modified resin. The modified resin, the SGP laminated resin and diisopropylbenzene peroxide are mixed, and the temperature of the feeding section is 190° C., the temperature of the melting section is 180° C., and the temperature of the discharging section is 150° C. The laminated sheet is obtained by extrusion casting to form a film, and the laminated sheet is placed between two pieces of glass and pressed at high temperature to obtain SGP laminated glass.
[0031] The molar ratio of the isocyanate group and ethylenediamine on the modified prepolymer in step S1 is 1:1, and the molar ratio of the hydroxyl group, diphenylmethane diisocyanate and N-(2-hydroxyethyl)maleimide on the pretreated polyurethane is 1:1:2.
[0032] The amount ratio of the modified polyurethane, modified filler, dimethyldiethoxysilane, ethanol, DMF, deionized water, hydrochloric acid solution and tetrabutyl titanate described in step S2 is 5g:80mg:1mmo l:10mL:50mL:20mL:3mL:1.5mmo l, the mass fraction of the hydrochloric acid solution is 10%, and the weight ratio of the modified resin and the SGP interlayer resin is 30:80:1.
[0033] The modified prepolymer is prepared by the following steps:
[0034] Step A1: p-Chloro-o-nitroaniline, p-hydroxystyrene, sodium nitrite and potassium hydrogen sulfate are mixed evenly and placed in a mortar, and ground for 20 minutes at a temperature of 20° C. to obtain an azo dye; the azo dye, ethanol and sodium hydroxide solution are mixed evenly, and sodium dithionite is added under stirring at a speed of 600 r / min and a temperature of 80° C., and the mixture is reacted for 1 hour to obtain an intermediate 1;
[0035] Step A2: Mix magnesium metal, iodine and tetrahydrofuran evenly, introduce nitrogen protection, stir and add 2-bromothiophene at a speed of 60 r / min and a temperature of 20° C., raise the temperature to 60° C., and react for 3 h to obtain intermediate 2; mix intermediate 1, intermediate 2 and tetrahydrofuran evenly, and react at a speed of 150 r / min and a temperature of 60° C. for 5 h to obtain a modifier;
[0036] Step A3: The modifier, diethanolamine and DMF are mixed evenly, nitrogen is introduced for protection, and sodium hydroxide is added to the mixture at a speed of 120 r / min and a temperature of 20°C until the pH value is 10, and the reaction is carried out for 3 hours. The pH is adjusted to be neutral to obtain a modified monomer, and the modified monomer, diphenylmethane diisocyanate and DMF are mixed, and the reaction is carried out at a speed of 120 r / min and a temperature of 40°C for 2 hours to obtain a modified prepolymer.
[0037] The molar ratio of p-chloro-o-nitroaniline, p-hydroxystyrene, sodium nitrite and potassium hydrogen sulfate described in step A1 is 1:1.1:1:1, and the amount ratio of azo dye, ethanol, sodium hydroxide solution and sodium dithionite is 25 mmol:50 mL:50 mL:82 mmol.
[0038] The amount ratio of magnesium metal, iodine, tetrahydrofuran and 2-bromothiophene described in step A2 is 1.1 mol:1 mol:100 mL:1 mol, and the molar ratio of intermediate 1 to intermediate 2 is 1:1.
[0039] The molar ratio of the modifier described in step A3 to diethanolamine is 1:1, and the molar ratio of the modified monomer to diphenylmethane diisocyanate is 1:2.1.
[0040] The modified filler is prepared by the following steps:
[0041] Step B1: triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate and deionized water are mixed uniformly, stirred at a speed of 150 r / min and a temperature of 80°C, and tetraethyl orthosilicate, KH550 and ethanol are added, reacted for 4 hours, centrifuged to remove the supernatant, the substrate is added to a hydrochloric acid solution, ultrasonically treated for 5 minutes at a frequency of 20 kHz and a temperature of 20°C, and then heated to 60°C and kept warm for 5 hours to obtain amino-modified nano-silica;
[0042] Step B2: Evenly mix the amino-modified nano-silica, tin tetrachloride and ethanol, stir and add deionized water and ammonia water to a pH of 10 at a speed of 120 r / min and a temperature of 30°C, stir for 10 minutes, heat to 150°C, and react for 20 hours to obtain modified nano-silica, disperse the modified nano-silica in ethanol, introduce nitrogen protection, stir and add 3-isocyanatepropyltriethoxysilane at a speed of 300 r / min and a temperature of 30°C, and react for 2 hours to obtain a modified filler.
[0043] The amount ratio of triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate, deionized water, tetraethyl orthosilicate, KH550 and ethanol described in step B1 is 65mg:380mg:550mg:25mL:10mmo l:5mmo l:5mL, the amount ratio of base material and hydrochloric acid solution is 1mg:1mL, and the mass fraction of hydrochloric acid solution is 5%.
[0044] The amount ratio of the amino-modified nano-silica, tin tetrachloride, ethanol and deionized water described in step B2 is 2g:2mmo l:10mL:10mL, and the molar ratio of the amino group on the surface of the modified nano-silica and 3-isocyanatepropyltriethoxysilane is 1:1.
[0045] Example 2
[0046] A production process of SGP film laminated glass, specifically comprising the following steps:
[0047] Step S1: the modified prepolymer, ethylenediamine and DMF are mixed, nitrogen is introduced for protection, the reaction is carried out for 3 hours at a speed of 150 r / min and a temperature of 35° C., KH560 is added, the pH value is adjusted to 11, and the reaction is carried out for 4 hours to obtain a pretreated polyurethane; the pretreated polyurethane, diphenylmethane diisocyanate and DMF are mixed, nitrogen is introduced for protection, the reaction is carried out for 6 hours at a speed of 150 r / min and a temperature of 35° C., N-(2-hydroxyethyl)maleimide is added, and the reaction is continued for 5 hours to obtain a modified polyurethane;
[0048] Step S2: The modified polyurethane, the modified filler, the dimethyldiethoxysilane, the ethanol and the DMF are mixed uniformly, and the mixture is stirred and deionized water and hydrochloric acid are added at a speed of 120 r / min and a temperature of 68° C. After reacting for 3 hours, tetrabutyl titanate is added, and the reaction is continued for 2 hours. The mixture is heated to 125° C. and reacted for 4 hours to obtain a modified resin. The modified resin, the SGP laminated resin and diisopropylbenzene peroxide are mixed, and the temperature of the feeding section is 190° C., the temperature of the melting section is 180° C., and the temperature of the discharging section is 150° C. The laminated sheet is obtained by extrusion casting to form a film, and the laminated sheet is placed between two pieces of glass and pressed at high temperature to obtain SGP laminated glass.
[0049] The molar ratio of the isocyanate group and ethylenediamine on the modified prepolymer in step S1 is 1:1, and the molar ratio of the hydroxyl group, diphenylmethane diisocyanate and N-(2-hydroxyethyl)maleimide on the pretreated polyurethane is 2:2:2.
[0050] The amount ratio of the modified polyurethane, modified filler, dimethyldiethoxysilane, ethanol, DMF, deionized water, hydrochloric acid solution and tetrabutyl titanate described in step S2 is 5g:80mg:1mmo l:10mL:50mL:20mL:3mL:1.5mmo l, the mass fraction of the hydrochloric acid solution is 10%, and the weight ratio of the modified resin and the SGP interlayer resin is 40:90:2.
[0051] The modified prepolymer is prepared by the following steps:
[0052] Step A1: p-Chloro-o-nitroaniline, p-hydroxystyrene, sodium nitrite and potassium hydrogen sulfate were mixed evenly and placed in a mortar, and ground for 25 minutes at a temperature of 20° C. to obtain an azo dye; the azo dye, ethanol and sodium hydroxide solution were mixed evenly, and sodium dithionite was added under stirring at a speed of 600 r / min and a temperature of 80° C., and the mixture was reacted for 1.5 hours to obtain an intermediate 1;
[0053] Step A2: Mix magnesium metal, iodine and tetrahydrofuran evenly, introduce nitrogen protection, stir and add 2-bromothiophene at a speed of 60 r / min and a temperature of 25° C., heat to 65° C., and react for 4 hours to obtain intermediate 2; mix intermediate 1, intermediate 2 and tetrahydrofuran evenly, and react at a speed of 150 r / min and a temperature of 65° C. for 6 hours to obtain a modifier;
[0054] Step A3: The modifier, diethanolamine and DMF are mixed evenly, nitrogen is introduced for protection, and sodium hydroxide is added to the mixture at a speed of 150 r / min and a temperature of 20°C until the pH value is 10, and the reaction is carried out for 4 hours. The pH is adjusted to be neutral to obtain a modified monomer, and the modified monomer, diphenylmethane diisocyanate and DMF are mixed, and the reaction is carried out at a speed of 120 r / min and a temperature of 45°C for 3 hours to obtain a modified prepolymer.
[0055] The molar ratio of p-chloro-o-nitroaniline, p-hydroxystyrene, sodium nitrite and potassium hydrogen sulfate described in step A1 is 1:1.1:1:1, and the amount ratio of azo dye, ethanol, sodium hydroxide solution and sodium dithionite is 25 mmol:50 mL:50 mL:82 mmol.
[0056] The amount ratio of magnesium metal, iodine, tetrahydrofuran and 2-bromothiophene described in step A2 is 1.1 mol:1 mol:100 mL:1 mol, and the molar ratio of intermediate 1 to intermediate 2 is 1:1.
[0057] The molar ratio of the modifier described in step A3 to diethanolamine is 1:1, and the molar ratio of the modified monomer to diphenylmethane diisocyanate is 1:2.1.
[0058] The modified filler is prepared by the following steps:
[0059] Step B1: triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate and deionized water are mixed uniformly, stirred at a speed of 150 r / min and a temperature of 85° C., and tetraethyl orthosilicate, KH550 and ethanol are added, reacted for 5 hours, centrifuged to remove the supernatant, the substrate is added to a hydrochloric acid solution, ultrasonically treated for 8 minutes at a frequency of 25 kHz and a temperature of 20° C., and then heated to 65° C. and kept warm for 6 hours to obtain amino-modified nano-silica;
[0060] Step B2: Evenly mix the amino-modified nano-silica, tin tetrachloride and ethanol, stir and add deionized water and ammonia water to a pH of 10 at a speed of 150 r / min and a temperature of 35°C, stir for 10 minutes, heat to 155°C, and react for 23 hours to obtain modified nano-silica. Disperse the modified nano-silica in ethanol, introduce nitrogen protection, stir and add 3-isocyanatepropyltriethoxysilane at a speed of 500 r / min and a temperature of 35°C, and react for 2 hours to obtain a modified filler.
[0061] The amount ratio of triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate, deionized water, tetraethyl orthosilicate, KH550 and ethanol described in step B1 is 65mg:380mg:550mg:25mL:10mmo l:5mmo l:5mL, the amount ratio of base material and hydrochloric acid solution is 1mg:1mL, and the mass fraction of hydrochloric acid solution is 5%.
[0062] The amount ratio of the amino-modified nano-silica, tin tetrachloride, ethanol and deionized water described in step B2 is 2g:2mmo l:10mL:10mL, and the molar ratio of the amino group on the surface of the modified nano-silica and 3-isocyanatepropyltriethoxysilane is 1:1.
[0063] Example 3
[0064] A production process of SGP film laminated glass, specifically comprising the following steps:
[0065] Step S1: the modified prepolymer, ethylenediamine and DMF are mixed, nitrogen is introduced for protection, the reaction is carried out for 3 hours at a speed of 200 r / min and a temperature of 40° C., KH560 is added, the pH value is adjusted to 12, and the reaction is carried out for 5 hours to obtain a pretreated polyurethane; the pretreated polyurethane, diphenylmethane diisocyanate and DMF are mixed, nitrogen is introduced for protection, the reaction is carried out for 6 hours at a speed of 200 r / min and a temperature of 40° C., N-(2-hydroxyethyl)maleimide is added, and the reaction is continued for 6 hours to obtain a modified polyurethane;
[0066] Step S2: The modified polyurethane, the modified filler, the dimethyldiethoxysilane, the ethanol and the DMF are mixed uniformly, and the mixture is stirred and deionized water and hydrochloric acid are added at a speed of 150 r / min and a temperature of 70° C. After reacting for 3 hours, tetrabutyl titanate is added, and the reaction is continued for 3 hours. The mixture is heated to 130° C. and reacted for 5 hours to obtain a modified resin. The modified resin, the SGP laminated resin and diisopropylbenzene peroxide are mixed, and the temperature of the feeding section is 190° C., the temperature of the melting section is 180° C., and the temperature of the discharging section is 150° C. The laminated sheet is obtained by extrusion casting to form a film, and the laminated sheet is placed between two pieces of glass and pressed at high temperature to obtain SGP laminated glass.
[0067] The molar ratio of the isocyanate group and ethylenediamine on the modified prepolymer in step S1 is 1:1, and the molar ratio of the hydroxyl group, diphenylmethane diisocyanate and N-(2-hydroxyethyl)maleimide on the pretreated polyurethane is 3:3:2.
[0068] The amount ratio of the modified polyurethane, modified filler, dimethyldiethoxysilane, ethanol, DMF, deionized water, hydrochloric acid solution and tetrabutyl titanate described in step S2 is 5g:80mg:1mmo l:10mL:50mL:20mL:3mL:1.5mmo l, the mass fraction of the hydrochloric acid solution is 10%, and the weight ratio of the modified resin and the SGP interlayer resin is 50:100:3.
[0069] The modified prepolymer is prepared by the following steps:
[0070] Step A1: p-Chloro-o-nitroaniline, p-hydroxystyrene, sodium nitrite and potassium hydrogen sulfate are mixed evenly and placed in a mortar, and ground for 30 minutes at a temperature of 25° C. to obtain an azo dye; the azo dye, ethanol and sodium hydroxide solution are mixed evenly, and sodium dithionite is added under stirring at a speed of 800 r / min and a temperature of 85° C., and the mixture is reacted for 1.5 hours to obtain an intermediate 1;
[0071] Step A2: Mix magnesium metal, iodine and tetrahydrofuran evenly, introduce nitrogen protection, stir and add 2-bromothiophene at a speed of 80 r / min and a temperature of 25° C., heat to 70° C., and react for 5 h to obtain intermediate 2; mix intermediate 1, intermediate 2 and tetrahydrofuran evenly, and react at a speed of 200 r / min and a temperature of 70° C. for 6 h to obtain a modifier;
[0072] Step A3: The modifier, diethanolamine and DMF are mixed evenly, nitrogen is introduced for protection, and sodium hydroxide is added to the mixture at a speed of 150 r / min and a temperature of 25°C until the pH value reaches 11, and the reaction is carried out for 5 hours. The pH is adjusted to be neutral to obtain a modified monomer, and the modified monomer, diphenylmethane diisocyanate and DMF are mixed, and the reaction is carried out at a speed of 150 r / min and a temperature of 50°C for 4 hours to obtain a modified prepolymer.
[0073] The molar ratio of p-chloro-o-nitroaniline, p-hydroxystyrene, sodium nitrite and potassium hydrogen sulfate described in step A1 is 1:1.1:1:1, and the amount ratio of azo dye, ethanol, sodium hydroxide solution and sodium dithionite is 25 mmol:50 mL:50 mL:82 mmol.
[0074] The amount ratio of magnesium metal, iodine, tetrahydrofuran and 2-bromothiophene described in step A2 is 1.1 mol:1 mol:100 mL:1 mol, and the molar ratio of intermediate 1 to intermediate 2 is 1:1.
[0075] The molar ratio of the modifier described in step A3 to diethanolamine is 1:1, and the molar ratio of the modified monomer to diphenylmethane diisocyanate is 1:2.1.
[0076] The modified filler is prepared by the following steps:
[0077] Step B1: triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate and deionized water are uniformly mixed, and under the conditions of a rotation speed of 200 r / min and a temperature of 85° C., tetraethyl orthosilicate, KH550 and ethanol are added with stirring, and the reaction is carried out for 6 hours, and the supernatant is removed by centrifugation, and the substrate is added to a hydrochloric acid solution, and under the conditions of a frequency of 30 kHz and a temperature of 25° C., an ultrasonic treatment is carried out for 10 minutes, and then the temperature is raised to 70° C. and kept warm for 7 hours to obtain amino-modified nano-silica;
[0078] Step B2: Evenly mix the amino-modified nano-silica, tin tetrachloride and ethanol, stir and add deionized water and ammonia water to a pH of 12 at a speed of 150 r / min and a temperature of 40°C, stir for 15 minutes, heat to 160°C, and react for 25 hours to obtain modified nano-silica, disperse the modified nano-silica in ethanol, introduce nitrogen protection, stir and add 3-isocyanatepropyltriethoxysilane at a speed of 500 r / min and a temperature of 40°C, and react for 3 hours to obtain a modified filler.
[0079] The amount ratio of triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate, deionized water, tetraethyl orthosilicate, KH550 and ethanol described in step B1 is 65mg:380mg:550mg:25mL:10mmo l:5mmo l:5mL, the amount ratio of base material and hydrochloric acid solution is 1mg:1mL, and the mass fraction of hydrochloric acid solution is 5%.
[0080] The amount ratio of the amino-modified nano-silica, tin tetrachloride, ethanol and deionized water described in step B2 is 2g:2mmo l:10mL:10mL, and the molar ratio of the amino group on the surface of the modified nano-silica and 3-isocyanatepropyltriethoxysilane is 1:1.
[0081] Comparative Example 1
[0082] Compared with Example 1, this comparative example uses nano silicon dioxide instead of the modified filler, and the other steps are the same.
[0083] Comparative Example 2
[0084] Compared with Example 1, this comparative example uses amino-treated nano-silica instead of modified nano-silica, and the remaining steps are the same.
[0085] Comparative Example 3
[0086] Compared with Example 1, this comparative example uses diphenylmethane diisocyanate instead of the modified prepolymer, and the remaining steps are the same.
[0087] Comparative Example 4
[0088] Compared with Example 1, this comparative example uses SGP interlayer sheet instead of interlayer sheet, and the other steps are the same.
[0089] The laminated glass and ordinary glass prepared in Examples 1-3 and Comparative Examples 1-4 were made into a 1m 3 Samples of different sizes were artificially exposed to simulated sunlight for 8 hours and the temperature difference was compared with that in ordinary glass space. The test results are shown in the following table.
[0090]
[0091] It can be seen from the above table that this application has a very good thermal insulation effect.
[0092] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A production process of SGP film laminated glass, characterized by: The specific steps include: Step S1: the modified prepolymer, ethylenediamine and DMF are mixed, nitrogen is introduced for protection, and after the reaction, KH560 is added to react to obtain a pretreated polyurethane; the pretreated polyurethane, diphenylmethane diisocyanate and DMF are mixed, nitrogen is introduced for protection, and after the reaction, N-(2-hydroxyethyl)maleimide is added to continue the reaction to obtain a modified polyurethane; Step S2: The modified polyurethane, the modified filler, the dimethyldiethoxysilane, the ethanol and the DMF are mixed and stirred, and deionized water and hydrochloric acid are added to react, and then tetrabutyl titanate is added to continue the reaction to obtain a modified resin, and the modified resin, the SGP laminated resin and the diisopropylbenzene peroxide are mixed and extruded to form a film to obtain a laminated sheet, and the laminated sheet is placed between two pieces of glass and pressed at high temperature to obtain SGP film laminated glass.
2. The production process of SGP film laminated glass according to claim 1, characterized in that: The modified prepolymer is prepared by the following steps: Step A1: p-chloro-o-nitroaniline, p-hydroxystyrene, sodium nitrite and potassium hydrogen sulfate are uniformly mixed and placed in a mortar, and ground to obtain an azo dye; the azo dye, ethanol and sodium hydroxide solution are mixed and stirred, and sodium dithionite is added to react to obtain an intermediate 1; Step A2: Mix magnesium metal, iodine and tetrahydrofuran evenly, introduce nitrogen protection, stir and add 2-bromothiophene to react to obtain intermediate 2, and mix intermediate 1, intermediate 2 and tetrahydrofuran to react to obtain a modifier; Step A3: uniformly mix the modifier, diethanolamine and DMF, introduce nitrogen protection, stir and add sodium hydroxide to react, adjust the pH to neutral to obtain a modified monomer, and mix the modified monomer, diphenylmethane diisocyanate and DMF to obtain a modified prepolymer.
3. The production process of SGP film laminated glass according to claim 2, characterized in that: The molar ratio of p-chloro-o-nitroaniline, p-hydroxystyrene, sodium nitrite and potassium hydrogen sulfate described in step A1 is 1:1.1:1:1, and the amount ratio of azo dye, ethanol, sodium hydroxide solution and sodium dithionite is 25mmol:50mL:50mL:82mmol.
4. The production process of SGP film laminated glass according to claim 2, characterized in that: The amount ratio of magnesium metal, iodine, tetrahydrofuran and 2-bromothiophene in step A2 is 1.1 mol: 1 mol: 100 mL: 1 mol, and the molar ratio of intermediate 1 to intermediate 2 is 1:
1.
5. The production process of SGP film laminated glass according to claim 2, characterized in that: The molar ratio of the modifier described in step A3 to diethanolamine is 1:1, and the molar ratio of the modified monomer to diphenylmethane diisocyanate is 1:2.
1.
6. The production process of SGP film laminated glass according to claim 1, characterized in that: The modified filler is prepared by the following steps: Step B1: triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate and deionized water are mixed and stirred, and tetraethyl orthosilicate, KH550 and ethanol are added, and after reaction, the supernatant is removed by centrifugation, and the substrate is added to a hydrochloric acid solution, and after ultrasonic treatment, the temperature is increased and kept to obtain amino-modified nano-silica; Step B2: Mix and stir the amino-modified nano-silica, tin tetrachloride and ethanol, add deionized water and ammonia water, stir, and heat to react to obtain modified nano-silica. Disperse the modified nano-silica in ethanol, introduce nitrogen protection, stir, add 3-isocyanatepropyltriethoxysilane, and react to obtain a modified filler.
7. The production process of SGP film laminated glass according to claim 6, characterized in that: The amount ratio of triethanolamine, hexadecyltrimethylammonium bromide, sodium trifluoroacetate, deionized water, tetraethyl orthosilicate, KH550 and ethanol in step B1 is 65 mg:380 mg:550 mg:25 mL:10 mmol:5 mmol:5 mL, and the amount ratio of the base material and the hydrochloric acid solution is 1 mg:1 mL.
8. The production process of SGP film laminated glass according to claim 6, characterized in that: The amount ratio of the amino-modified nano-silica, tin tetrachloride, ethanol and deionized water described in step B2 is 2g:2mmol:10mL:10mL, and the molar ratio of the amino group on the surface of the modified nano-silica and 3-isocyanatepropyltriethoxysilane is 1:
1.
9. A production process of SGP film laminated glass, characterized by: Produced according to any one of the production processes described in claims 1-8.
Citation Information
Patent Citations
Solid polymeric substrate having adherent resin component derived from curable silylated polyurethane composition
CN101535360A
Sewing-free hot melt adhesive TPU leather and preparation method thereof
CN103437194A
SGP photographic film with heat-insulating effect and preparation method therefor
CN107858110A
Novel environment-friendly silane graft modified polymer (SGP) elastic layer material and preparation method thereof
CN111154254A
High-water-resistance waterborne acrylic polyurethane and preparation method thereof
CN115286761A
Cited By
Nanometer silicon-based heat-insulation fireproof glass film and preparation method thereof
CN119974707A
A nano-silicon-based heat-insulating and fireproof glass film and its preparation method
CN119974707B
Poly (p-hydroxystyrene) resin as well as preparation method and application thereof
CN120923798A
Near-infrared response self-repairing coating and preparation method thereof
CN122011918A